Patient Access: Improving Wait Times in a Specialty Clinic. Issue 1 (January 2016) - Kwong, Tarina
Abstract : A vascular surgery clinic in an academic center faced many delays for patients in gaining access to an appointment. In January 2014, wait times from referral to patient appointment were estimated to be 3 to 4 weeks. A 6-month pilot project was conducted from January 2014 through June 2014 with the aim of scheduling 50% of new patients within 7 days of referral. The clinic manager, medical director, clinic staff, and clerical team worked in partnership to initiate a series of interventions to reduce the backlog of patients, implement scheduling guidelines, and use nurse practitioners to improve practice efficiencies. By June 2014, the vascular surgery clinic achieved the goals of increased accommodation of new patients and a positive trend patient satisfaction comments as surveyed by Press Ganey. Performance outcomes in both areas were sustained for 6 consecutive months.